YouTube as a source of patient information for transrectal ultrasound-guided biopsy of the prostate. Issue 1 (January 2019) - Jain, N.; Abboudi, H.; Kalic, A.; Gill, F.; Al-Hasani, H.
Abstract : Aim: To assess the quality of YouTube videos explaining transrectal ultrasound (TRUS)-guided biopsies of the prostate. Materials and methods: A search of YouTube was made for the terms "TRUS", "TRUS biopsy", "transrectal ultrasound", and "prostate biopsy". Videos were selected from the first 10 pages of results and reviewed by three authors against criteria based on written information from the British Association of Urological Surgeons. They were given a qualitative rating based on how well they provided information on factors such as preparation for the procedure, mechanism of the procedure and possible side effects. Data were also collected on view count, country of origin, likes, and dislikes. Results: A total of 41 videos were reviewed, with no videos achieving an "excellent" rating, 32 being rated as "very poor", and only one rated as "good". Despite the poor-quality information, 39 of the videos were from healthcare organisations or individual surgeons. Videos often lacked specific information, or were targeted at healthcare professionals instead of patients. Conclusion: The information about TRUS-guided prostate biopsies on YouTube was not of a sufficiently high standard to allow patients to make informed decisions. Healthcare professionals hence have a duty to point patients towards adequate sources of reputable information online. Furthermore, there remains an opportunity to produce high-quality, informative, patient-focussed medical YouTube videos. Highlights: YouTube provides an ever-growing, unregulated source of patient information. The quality of YouTube information for TRUS biopsies was found to be poor. We cannot recommend YouTube as a source of information for informed decision-making. There are opportunities to produce reputable, high-quality medical YouTube videos.